The algebra of multirelations. (June 2013) - MARTIN, C. E.; CURTIS, S. A.
<x content-type="archive" xml:space="preserve">Abstract</x> Multirelational semantics are well suited to reasoning about programs involving two kinds of non-determinism. This paper lays the categorical foundations for an algebraic calculus of multirelations.